Cambios morfológicos y formación de anillos de crecimiento por estrés hídrico bajo condiciones controladas en plantas de Cedrela montana Moritz ex Turcz y Handroanthus chrysanthus (Jacq.) S.O.Grose en el cantón Loja, Ecuador - Quezada Armijos, Jefferson Iván (2022)
The internal morphology changes and anatomical structure of the plant are consequences of the environmental variations. However, not exactly known how the forest species in our environment react to the water stress nor what their adaptation strategies are. Therefore, Cedrela montana and Handroanthus chrysanthus were selected as representative species of the ecosystems with different precipitation regimes for this experiment in controlled conditions under greenhouse. The objective was to evaluate how the water stress influences morphology and the tree rings formation. For this reason, four water stress treatments was established (T1-T4) and a control (T0) with 20 individuals each. Evaluated during 24 months each 15 days with a continuous register the height, diameter, number of leaves, mortality and phytosanitary status. At the Laboratorio de Anatomía de Maderas Tropicales - UNL transverse anatomical sections of stem were performed, and with the software ICY Bioimage Analysis the different anatomical tissues were characterized. Through the programming environment R, the statistics data analysis was performed, with non-parametric tests of Kruskal-Wallis and Wilcoxon (α = 0, 05), with boxplot and graph of vertices. With morphology relation, Cedrela montana did not have significant differences between T0 and the water stress treatments (α = 0, 05; p-value > 0, 05). On the other hand, Handroanthus chrysanthus showed significant differences between the water stress treatments (α = 0, 05; p-value > 0, 05) and the control. Furthermore, Cedrela montana had the 2, 58% and Handroanthus chrysanthus 34, 8% of mortality in the water stress treatments. The morphological development Cedrela montana was independent of the type of water stress to which it was subjected, showing an efficient resistance to adverse conditions. Instead, Handroanthus chrysanthus was more vulnerable in long periods of water stress. At the anatomic level Cedrela montana showed a faster regeneration of the vascular cambium caused by a strong incision in the xylem, while the Handroanthus chrysanthus was more vulnerable in long periods of water stress. Both tree species created incomplete or false rings, just the Handroanthus chrysanthus tree-rings showed a few relation with the diametric instrumental measurements. Key words: Water stress, morphological development, tree ring.